2019
DOI: 10.3892/mmr.2019.10403
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of microRNA‑18a‑5p in oral squamous cell carcinoma

Abstract: The purpose of this study was mainly to explore the role and mechanism of microRNA-18a-5p (miR-18a-5p) in oral squamous cell carcinoma (OSCC). The expression of miR-18a-5p in OSCC cells and normal cells was firstly detected using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The cell viability, apoptosis, migration and invasion abilities of OSCC cells were determined by MTT, cell apoptosis, wound healing and Transwell assays respectively. Additionally, bioinformatics software analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A possible explanation to these contrasting reports regarding the expression and biological role of miR-18a is that depending on the tumor cell type, miR-18a regulates a particular group of genes, some with oncogenic roles and others with tumor-suppressive capabilities. For example, Huang et al observed that Smad2, a downstream effector of the TGFb signaling and a potent tumor suppressor in several cancers, is a major target of miR-18a in oral squamous cell carcinoma (34). The tumor suppressor genes PTEN and IRF2 have also been reported as direct targets of miR-18a in osteosarcoma (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation to these contrasting reports regarding the expression and biological role of miR-18a is that depending on the tumor cell type, miR-18a regulates a particular group of genes, some with oncogenic roles and others with tumor-suppressive capabilities. For example, Huang et al observed that Smad2, a downstream effector of the TGFb signaling and a potent tumor suppressor in several cancers, is a major target of miR-18a in oral squamous cell carcinoma (34). The tumor suppressor genes PTEN and IRF2 have also been reported as direct targets of miR-18a in osteosarcoma (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huang et al. observed that Smad2, a downstream effector of the TGF-β signaling and a potent tumor suppressor in several cancers, is a major target of miR-18a in oral squamous cell carcinoma ( 34 ). The tumor suppressor genes PTEN and IRF2 have also been reported as direct targets of miR-18a in osteosarcoma ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the TGF-β1 pathway, Smad2 and Smad3 are receptor-regulated effector proteins, and TGF-β induces apoptosis through Smad-mediated expression of death-associated protein kinase ( 141 ). Recently, Huang and colleagues ( 142 ) investigated the role and mechanism of miR−18a-5p in OSCC and it was revealed that miR−18a-5p was highly expressed in SCC9 cells compared with normal cells. Then the effect of miR−18a-5p upregulation and miR−18a-5p downregulation was investigated on SCC9 cell viability, migration, invasion and apoptosis.…”
Section: Biogenesis and Function Of Micrornas And Their Roles In Prog...mentioning
confidence: 99%
“…It plays an important role in deregulation of malignancies [ 6–8 ], which is closely associated with oncogene and progression of tumors through affecting the cellular process, such as cell growth and metastasis [ 9 , 10 ]. Hence, miRNAs are considered as important biomarkers and therapeutic targets in several types of cancers [ 11 , 12 ]. In NSCLC, the miR-199a-5p was reported to be targeted with MAP3K11 to inhibit cell progression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%